Diversity Pattern of Climbing Plants in Relation to Aquatic Sources in Fragmented Wild Patches - Manna, Saikat; Manna, Sumit; Roy, Anirban (Indian Forester, 2021)
Climbing plants play pivotal role in maintaining the structure and function of tropical ecosystems including fragmented wild patches. Besides the phorophytes, water sources are very significant to the climbers for their diversity and abundance. Being opportunistic in nature, climbing plants have to quest for easy access to water sources. Fragmented wild patches foster to sustain the diversity and abundance of climbing plants. The major objective of the present study is to understand the influence of aquatic sources on the diversity patterns of climbing plants in fragmented wild patches. Thirty such wild patches in the western lateritic region of West Bengal, India were selected for the present study. These wild patches were divided into three categories (with 10 patches in each) based on types of available water sources (i.e. lentic/lotic) and its absence. Individual counts of every species of trees and climbing plants was done in each patch for performing dissimilarity analysis. Study reveals that water sources are one of the key factors for the diversity patterns irrespective of soil types. Result shows that maximum dissimilarity lies between the patches adjacent to lentic system and those are not close to any water source. Dissimilarity was highest between patches with lentic and patches with lotic system in case of climbers with secondary growth. These findings would be helpful in the management of degraded forest patches especially through intervention of maintaining essential diversity and coverage of climbing plants with necessary aquatic sources.